Growing A Technopreneurship-Based New Entrepreneur In Business Incubator - Kunto Adi; Erlyna Wida Riptanti; Heru Irianto (Asian Journal of Innovation and Entrepreneurship, 2017)
Activity-based growth of new entrepreneurs at the Business Incubator's Technopreneurship general aim is to increase the capacity building of Business Incubator Unit PSP-MSME and SME tenants so as to improve students technoprenership-based entrepreneurship. Special Interest devotion second year: 1) Develop a productive unit that has been established in the first year, 2) Conducting the process of recruitment and selection of candidates SME tenants from students or alumni of UNS, 3) Improve the skills and knowledge of the field of productive business tenant.The results of activities in the second year are selected 10 tenants who pass the program to continue the business of fruit chips "Amaji Food". The tenant learned from the process of procurement of raw materials, production processes, packaging to marketing. Various exhibitions are also attended by the tenant in introducing the product "Amaji Food" to the public. The tenant also diversified its new products started to produce chips, carrots, radishes, beans and pumpkin. However, the new product is still in early stages of introduction to the market to evaluate the response of the market.Â